Short note : rape a consequence of Covid-19 quarantine on children and the elderly : a call for action - Grace Emmanuel Kaka,; Muhamad Helmi Md Said,; Shahrul Mizan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The novel coronavirus (Covid-19) led to a shift in the social structure of global cities leading to self-isolation and social/physical distancing to curb the spread of the virus. While these two are stand as good policy, they are greeted by domestic violence and rape as the most prevalent consequences. The researchers examined the impact of lockdown on domestic violence in Nigeria based on frequency of news reports using content analysis of two online news reports and discovered a high prevalence of rape on children (0 - 17 years) and elderly (60 years and above). Hence it is suggested that the government should always be prepared for emergencies. Also, future polices should consider the interest of the most vulnerable in the society by providing safety measures.